2019
DOI: 10.1136/bmjsem-2018-000505
|View full text |Cite
|
Sign up to set email alerts
|

Italian consensus statement (2020) on return to play after lower limb muscle injury in football (soccer)

Abstract: Return to play (RTP) decisions in football are currently based on expert opinion. No consensus guideline has been published to demonstrate an evidence-based decision-making process in football (soccer). Our aim was to provide a framework for evidence-based decision-making in RTP following lower limb muscle injuries sustained in football. A 1-day consensus meeting was held in Milan, on 31 August 2018, involving 66 national and international experts from various academic backgrounds. A narrative review of the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 150 publications
0
14
0
1
Order By: Relevance
“…There are no validated imaging criteria to guide the decision of a safe RTP. To date, no study has suggested US to guide the RTP decision, but a few studies have focused on MRI following hamstring injury [ 101 , 102 , 103 , 104 ]. Normalization of increased signal intensities on MRI is therefore not required for a successful RTP, since the signal alterations also persist at different weeks after the clinical healing of the injury, suggesting that functional recovery advances structural recovery at imaging [ 9 ].…”
Section: Return To Training (Rtt) and Return To Play (Rtp)mentioning
confidence: 99%
See 2 more Smart Citations
“…There are no validated imaging criteria to guide the decision of a safe RTP. To date, no study has suggested US to guide the RTP decision, but a few studies have focused on MRI following hamstring injury [ 101 , 102 , 103 , 104 ]. Normalization of increased signal intensities on MRI is therefore not required for a successful RTP, since the signal alterations also persist at different weeks after the clinical healing of the injury, suggesting that functional recovery advances structural recovery at imaging [ 9 ].…”
Section: Return To Training (Rtt) and Return To Play (Rtp)mentioning
confidence: 99%
“…The RTT process should be as individualized as possible, to allow a safe and fast return after a muscle injury. Regarding this point, the Italian consensus conference gave useful advice [ 101 ]. General assessment about this process is made up of some key points: absence of clinical symptoms [ 105 , 106 , 107 ]; absence of pain or tenderness during muscle palpation [ 10 , 107 , 108 , 109 ]; absence of pain on passive and active stretching [ 110 ]; absence of pain on isometric, concentric and eccentric contraction [ 10 ]; completion of the prescribed rehabilitation program [ 108 ]; MRI and US imaging [ 111 , 112 ]; subjective feelings of the player taken into account [ 113 , 114 , 115 ].…”
Section: Return To Training (Rtt) and Return To Play (Rtp)mentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of occurrence of this lesion is mostly observed in sports requiring maximal contractions, such as soccer and track and field. In these sports, muscle injury mainly affects biarticular muscles, in particular those with high percentage of fast-twitch fibers [2,4]. Soleus-gastrocnemius lesions are the most common muscle injuries in high-speed running, although in other sports (i.e., soccer) hamstrings and the rectus femoris are most involved [4].…”
Section: Introductionmentioning
confidence: 99%
“…At the present time, there are several studies in the literature which try to identify if any radiological parameter can correlate with the recovery time [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%